R-loop immunoprecipitation: a method to detect R-loop interacting factors - Beghè, C; Gromak, N (Springer, 2022)
R-loops are non-B-DNA structures consisting of an RNA/DNA hybrid and a displaced single-stranded DNA. They arise during transcription and play important biological roles. However, perturbation of R-loop levels represents a source of DNA damage and genome instability resulting in human diseases, including cancer and neurodegeneration. In this chapter, we describe a protocol which allows detection of R-loop interactors using affinity purification with S9.6 antibody, specific for RNA/DNA hybrids, followed by Western blotting or mass spectrometry. Multiple specificity controls including addition of synthetic competitors and RNase H treatment are described to verify the specificity of identified R-loop-binding factors. The identification of new R-loop interacting factors and the characterization of their involvement in R-loop biology provides a powerful resource to study the role of these important structures in health and disease.